The Viability of Bali Cattle Epididymal Sperm with the Addition of Caffeine in Tris-Egg Yolk Diluents - Abd Wahab Hasyim; Oktora Dwi Putranti (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
The research aimed to examine the effect of caffeine's addition on diluents on Bali cattle epididymis' survival or sperm viability to get the right amount of caffeine. The epididymis collection was taken from the Slaughterhouse of Ternate City. Analysis of sperm vitality or viability was carried out in the Biotechnology Laboratory of Universitas Khairun. The methods in this research were by preparing egg yolk Tris solution treated with caffeine P0 (0 mg/ml), P2 (2 mg/ml), P4 (4 mg/ml), and P6 (6 mg/ml) with four replications, and then the epididymal sperm was inserted into each treatment. The epididymal sperm viability was calculated by evaluating the percentage of the number of living sperm. It compared to the dead sperm, which were observed microscopically by eosin-nigrosin staining. The data obtained were analyzed by one-way analysis of variance (ANOVA) to see if there were significant differences (P0.05) or very real (P0.01), the analysis were then continued with the Tukey-W-Procedure test with SPSS 18. The results show that administration of caffeine 2 mg/ml and 4 mg/ml (86.95% and 86.95%) have a significant effect on the sperm viability of epididymis compared with 0 mg/ml and 6 mg/ml (69.38% and 69.91%) treatments.